Photoluminescence of barium-calcium titanates obtained by the microwave-assisted hydrothermal method (MAH) - Souza, A. E. [UNESP]; Silva, R. A. [UNESP]; Santos, G. T. A. [UNESP]; Moreira, M. L.; Volanti, D. P. [UNESP]; Teixeira, S. R. [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2010)
Ba1-xCaxTiO3 (x = 0, 0.25, 0.50, 0.75, and 1.0) samples report the association of three types of clusters synthesized by the microwave-assisted hydrothermal at 140 degrees C for 40 min. In order to evaluate influence of structural order-disorder degree among them, photoluminescence (PL) emission, X-ray diffraction, FT-Raman spectroscopy and Ultraviolet-Visible absorption were used. The PL emission of the crystalline phases grows up with the calcium concentration and reaches the highest PL emission to 0.75 Ca concentration, which is supported by the symmetry break caused by the phase transition. This PL emission is higher than that of the CaTiO3 phase. (C) 2010 Elsevier B.V. All rights reserved.